Starting Treatment According to Guidelines Evaluation: a multicentre audit of HIV patients in the UK. (March 2013) - Reeves, I; Premchand, N; Schwenk, A; Brennan-Benson, P; Cumming, S; Lee, V; Whitehead, T
The aim of this audit was to assess whether HIV patients are being started on antiretroviral therapy (ART) according to British and European guidelines. Data were collected from the Survey of Prevalent HIV Infections Diagnosed (SOPHID) return for 2010 at five major HIV management centres in the UK. Data from this 3873 patient cohort revealed 52 patients who should have been receiving ART according to the guidelines but were not. Of these, 23 patients elected not to start ART despite clinical advice to the contrary. Information required to assist in the decision for earlier ART initiation (CD4 count 350–500 cells/μL) was missing for some patients. Clinicians must pay attention to the regular assessment of patients with a CD4 count of 351 -500 cells/μL so that all those who may benefit from earlier treatment are identified. Future research should investigate patient barriers to initiating therapy following recommendation by a clinician.